2010
DOI: 10.4251/wjgo.v2.i2.76
|View full text |Cite
|
Sign up to set email alerts
|

Experience with peritoneal mesothelioma at the Milan National Cancer Institute

Abstract: Diffuse malignant peritoneal mesothelioma (DMPM) is an uncommon and rapidly fatal tumor. Therapeutic options have traditionally been limited and ineffective. The biologic and molecular events correlated with poor responsiveness to therapy are still poorly understood. In recent years, an innovative treatment approach involving aggressive cytoreductive surgery (CRS) and perioperative intraperitoneal chemotherapy has reportedly resulted in improved outcome, as compared to historical controls. Since 1995, at the N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…In this context, TMM have been proposed to represent a reservoir of candidate targets for the development of novel therapeutic interventions for the disease [32]. …”
Section: Discussionmentioning
confidence: 99%
“…In this context, TMM have been proposed to represent a reservoir of candidate targets for the development of novel therapeutic interventions for the disease [32]. …”
Section: Discussionmentioning
confidence: 99%
“…Only patients with performance status (PS) < 2, in according with Eastern Cooperative Oncology Group (ECOG) (11) with primary PC (pseudomixoma peritonei and mesothelioma) and secondary (from ovarian, GI and selected cases of sarcoma origin), with possible complete cytoreduction and without extraperitoneal disease are selected to undergo CRS-HIPEC. Surgical and anaesthesiological procedures have been well assessed and standardized (12,13).…”
Section: Materials and Methods Materials And Methodsmentioning
confidence: 99%
“…Urano et al showed an excellent in vitro and in vivo thermal augmentation of cisplatin [56]. Current applied cisplatin-based HIPEC regimens are the "Sugarbaker Regimen" [57] and the "National Cancer Institute Milan Regimen" [58] ( Table 3). …”
Section: Cisplatinmentioning
confidence: 99%